STRATEGY OF THE INDONESIAN CONSULATE GENERAL IN DAVAO CITY TO PROMOTE TRADE RELATIONS BETWEEN THE SANGIHE ISLANDS AND GENERAL SANTOS CITY IN THE TUNA FISHING SECTOR - Al Madinah, Dinar; Nur Azizah (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
The tuna fisheries sector plays a crucial role in regional economic development and is a strategic commodity in Indonesia's maritime diplomacy. However, despite the geographical proximity between the Sangihe Islands in Indonesia and General Santos City in the southern Philippines, formal trade cooperation in the tuna sector was not realized until 2024. This study explores the strategies implemented by the Consulate General of the Republic of Indonesia in Davao City to strengthen tuna fishing trade relations between the Sangihe Islands and General Santos City. Data was collected through in-depth interviews with economic officials at the Consulate General of the Republic of Indonesia in Davao City, supported by secondary data from academic journals, official reports, and credible online sources. The findings indicate that the Consulate General of the Republic of Indonesia in Davao City has implemented comprehensive strategies as a facilitator, including document translation, facilitation of trade forums, promotional activities, and technical training on tuna handling by Philippine standards. These efforts resulted in the official export of three tons of fresh tuna from the Sangihe Islands in early 2024. In conclusion, the economic diplomacy of the Indonesian Consulate General in Davao City has played a key role in fostering sustainable trade relations and enhancing Indonesia's regional influence in Mindanao.